Pengaruh Modernisasi Sistem Adminnistrasi Perpajakan terhadap Kepatuhan Wajib Pajak - Sri Murdiati; Heni Puji Setyaningrum; Kuspriatin Dwi (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
This research aims: to determine the effect of modernization of organizational structure, modernization of organizational procedure, modernization of strategy organization, modernaziation of cultural organization simultaneously and partially on tax compliance. Data collection methods used were questionnaires. Population oh this research as many as 101 respondents, while the sample taken in this study amounted to 48 respondents. The data analysis method used is the analysis of multiple linier regresi along with classic assumption test, test hypotheses, as well as the coefficient of determination. The result of this study is the first hypothesis of all independent variables simultaneously affect the significant value of 0.000. The second hypothesis of modernization of organizational structure has no partial effect on the significant value of 0.386. The third hypothesis of modernization of organizational procedures has no partial effect on the significant value of 0.949. The fourth hypothetical modernization of organizational strategy had no partial effect on the significant value of 0.161. The fifth hypothesis of modernization of organizational cultural has a partial effect on the significant value of 0.001. The result of coefficient determination test obtained R2 value equal to 0,423 or 42,3%. It can be interpreted that 42.3% taxpayer compliance in this model is influenced by modernization of organizational structure, modernization of organizational procedures, modernization of strategy organization and modernization of cultural organization. While the rest of 57.7% influenced by other factors outside the model of this study.